Case Study of Community Empowerment by PT Borneo Indobara in Tanah Bumbu Regency: Future-Fit Society Strategy and Exit Strategy in the Development of an Integrated Poultry Farming Center - Tri Andi Subagiyo; Silvyna Aditia; Bilqis Nabila; I Komang Tri Febi Astawa (Green Publisher Indonesia, 2025)
This study explores a community empowerment initiative undertaken by PT Borneo Indobara, a coal mining company operating in Tanah Bumbu Regency, South Kalimantan, focusing on the development of an integrated poultry farming center. The research examines the strategic framework adopted by the company to align with the concept of a future-fit society, one that is resilient, inclusive, and economically sustainable beyond the lifespan of extractive industries. Through a qualitative case study approach, the paper investigates how PT Borneo Indobara integrates local potentials, stakeholder engagement, and capacity building in establishing a long-term productive economic unit for the surrounding community. The study finds that the establishment of the integrated poultry center is already underway, beginning with the implementation of a poultry farming program as an entry-point strategy for market creation. This initiative primarily aims to lay the foundation for the eventual development of a local livestock feed factory. The overall strategy envisions a self-sustaining and integrated value chain, spanning feed production, poultry farming, and product marketing, where each component supports the others, fostering local economic independence. Particular emphasis is placed on the company’s exit strategy, designed to ensure program continuity, community ownership, and institutional sustainability after the closure of mining operations.